A method for repairing nickel-based single crystal superalloy by laser cladding based on nanocomposites

CN117600470BActive Publication Date: 2026-10-20AIR FORCE UNIV PLA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311603551.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2026-10-20
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

上述修复方式虽然能够一定程度上避免上述缺陷的形成,但是制备的镍基单晶高温合金的组织中仍存在一定程度的表面裂纹、残余应力、气孔等问题的问题,仍限制了镍基单晶高温合金的进一步发展和应用

Benefits of technology

[0024]本发明从激光熔覆技术出发,完全优化改良相关金属粉末与技术思路,得到了单晶程度更高组织,更重要的是分析微观组织形貌,将外延单晶熔覆组织显微硬度与拉伸强度等性能提升到更高程度,优化了合金的服役性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117600470B_ABST
    Figure CN117600470B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of nickel-based single crystal superalloy laser cladding, and discloses a nickel-based single crystal superalloy laser cladding repair method based on nanocomposites, which comprises the following steps: grinding and uniformly mixing nickel-based superalloy powder and oxide nanoparticles to obtain mixed powder, and loading the mixed powder into a powder feeder; fixing the surface of a repaired substrate on a repair platform after pretreatment; adjusting the position of the powder feeder, setting the powder feeding rate and the working parameters of laser cladding, adopting a synchronous powder feeding mode, depositing the mixed powder on the surface of the repaired substrate to form an epitaxial cladding organization layer, and thus repairing the surface of the repaired substrate. Under the action of laser power, the mixed powder is deposited on the surface of the repaired substrate through a specific laser cladding process to realize epitaxial growth of single crystal superalloy laser cladding. The method can not only ensure that the cladding repair organization has good single crystal property, but also improve the mechanical properties of the cladding organization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser cladding technology for nickel-based single-crystal superalloys, and in particular to a method for repairing nickel-based single-crystal superalloys by laser cladding based on nanocomposite materials. Background Technology

[0002] Nickel-based single-crystal superalloys exhibit excellent ultimate strength and high-temperature corrosion resistance under high-temperature conditions (generally above 650℃), and are widely used in the field of aero-engine manufacturing.

[0003] However, nickel-based single-crystal superalloy turbine blades operate repeatedly under harsh conditions such as high temperature, high pressure, high speed, and high load inside the combustion chamber of aero-engines, making them prone to various types of surface defects, including surface wear, tip loss, and thermal crack fatigue. Due to the complex casting process, high precision requirements, and low manufacturing yield of single-crystal turbine blades, replacing damaged and scrapped turbine blades significantly increases maintenance costs. Furthermore, the supply cycle of new spare blades is often unreliable; without repair and remanufacturing of damaged blades, the maintenance cycle of aero-engines will be affected. Therefore, for nickel-based single-crystal superalloy turbine blades damaged in service, there is an urgent need to conduct research on key technologies in the international maintenance field, such as single-crystal blade growth repair and mechanical property restoration.

[0004] To address the aforementioned technical problems, those skilled in the art have proposed a relatively traditional laser cladding repair method for nickel-based single-crystal superalloys. This method involves remelting and cladding the surface of the nickel-based single-crystal superalloy to repair surface cracks. While this repair method can avoid the formation of the aforementioned defects to some extent, the microstructure of the prepared nickel-based single-crystal superalloy still exhibits certain surface cracks, residual stress, and porosity, thus limiting the further development and application of nickel-based single-crystal superalloys.

[0005] Therefore, this invention provides a method for laser cladding repair of nickel-based single-crystal superalloys based on nanocomposite materials. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials. This invention fully integrates nanoparticles into the original metal powder. Through a combination of computational simulation and experimentation, the parameters of the laser and CNC machine tool are adjusted to refine the primary dendrite spacing and maintain grain refinement during the cladding process. This aims to improve the dislocation density distribution within the epitaxial cladding structure and promote finer grain formation, ensuring good single-crystallinity of the epitaxial cladding structure while significantly improving its application mechanical properties.

[0007] The present invention provides a laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials, which is achieved through the following technical solution:

[0008] A laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials includes the following steps:

[0009] Nickel-based superalloy powder and oxide nanoparticles are ground together to disperse the nanoparticles in the nickel-based superalloy powder, thereby obtaining a mixed powder.

[0010] The surface of the substrate to be repaired is pretreated to obtain the pretreated substrate, and then it is fixed on the repair platform.

[0011] The mixed powder is loaded into the powder feeder, and the angle between the nozzle of the powder feeder and the surface of the substrate to be repaired is adjusted to 38-42°. The powder feeding rate of the powder feeder is set.

[0012] By setting the various working parameters of laser cladding and using a synchronous powder feeding method, the mixed powder is deposited on the surface of the substrate to be repaired to form an epitaxial cladding structure layer, thus completing the repair of the surface of the substrate to be repaired.

[0013] Preferably, the oxide nanoparticles are ZnO nanoparticles.

[0014] Preferably, the oxide nanoparticles have a particle size of 40–60 nm.

[0015] Preferably, the composition of the nickel-based superalloy powder is the same as that of the substrate to be repaired.

[0016] Preferably, the particle size of the nickel-based high-temperature alloy powder is 40–50 μm.

[0017] Preferably, the mass ratio of the nickel-based superalloy powder to the oxide nanoparticles is 9 to 11:1.

[0018] Preferably, the process parameters for laser cladding are as follows:

[0019] The laser power is 200–500W, the spot diameter is 700–900μm, the laser scanning speed is 10–20mm / s, the powder feeding rate is 10–15g / min, and the defocusing amount is -300–300μm.

[0020] Preferably, the grinding process is carried out by mechanical grinding, with a grinding speed of 80-120 r / min and a grinding time of 5-10 min.

[0021] Preferably, the preprocessing is performed through the following steps:

[0022] The surface of the substrate to be repaired is polished using sandpaper and alcohol to achieve a surface roughness Ra of 1.5 to 6.5.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] Starting from laser cladding technology, this invention completely optimizes and improves the relevant metal powders and technical ideas, resulting in a microstructure with a higher degree of single crystal. More importantly, by analyzing the microstructure morphology, the microhardness and tensile strength of the epitaxial single crystal cladding microstructure are improved to a higher level, thus optimizing the service performance of the alloy.

[0025] Furthermore, the repair method of this invention greatly alleviates the generation of cracks in epitaxial single-crystal growth structures, reduces surface defects in cladding structures, and improves the mechanical properties of epitaxial single-crystal cladding structures. This laser cladding repair method can improve existing laser cladding repair powders to enhance the relevant mechanical properties of single-crystal repair structures. Specifically, under a certain laser power, using cladding powder containing a certain amount of nanoparticles, and through a specific laser process, laser cladding epitaxial growth of single-crystal high-temperature alloys is achieved. While ensuring good single-crystality of the cladding repair structure, a laser repair technology method has been found that maximizes the improvement of the mechanical properties (high hardness, high Young's modulus, and room temperature tensile properties) of the cladding structure, making it suitable for laser additive repair and remanufacturing in aerospace, shipbuilding, and other fields. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the preparation process of the present invention;

[0027] Figure 2 SEM image of a single nickel-based single-crystal superalloy powder at the 50 μm scale;

[0028] Figure 3 SEM image of a single nickel-based single-crystal superalloy powder at the 20 μm scale;

[0029] Figure 4 SEM image of a single nickel-based single-crystal superalloy powder at the 1 μm scale;

[0030] Figure 5 This is a SEM image of the mixed powder in Example 1 at a scale of 50 μm;

[0031] Figure 6 This is a SEM image of the mixed powder in Example 1 at a scale of 20 μm;

[0032] Figure 7 This is a SEM image of the mixed powder in Example 1 at a scale of 500 nm;

[0033] Figure 8This is a cross-sectional SEM image of the epitaxial cladding structure layer formed in Comparative Example 1;

[0034] Figure 9 This is a cross-sectional SEM image of the epitaxial cladding structure layer formed in Example 1;

[0035] Figure 10 The XRD patterns of the epitaxial cladding layers formed in Comparative Example 1 and Example 1 are shown.

[0036] Figure 11 A high-resolution TEM image of the dislocation distribution in the epitaxial cladding structure layer formed in Comparative Example 1;

[0037] Figure 12 This is a high-resolution TEM image of the dislocation distribution in the epitaxial cladding structure layer formed in Example 1;

[0038] Figure 13 The results show the hardness test results of the epitaxial cladding layers formed in Comparative Example 1 and Example 1;

[0039] Figure 14 The Young's modulus test results are for the epitaxial cladding microstructures formed in Comparative Example 1 and Example 1.

[0040] Figure 15 Load-displacement curves of the epitaxial cladding microstructure formed in Comparative Example 1 and Example 1;

[0041] Figure 16 The results show the ultimate tensile strength test results of the epitaxial cladding microstructures formed in Comparative Example 1 and Example 1;

[0042] Figure 17 The room temperature tensile curves of the epitaxial cladding structures formed in Comparative Example 1 and Example 1 are shown. Detailed Implementation

[0043] This invention considers porosity, suboptimal microstructure, and the heat-affected zone as crucial parameters determining the properties of the cladding structure. When the aspect ratio of the cladding channel is unsuitable or the wettability is poor, voids will form between the channels. These interlayer voids often occur on adjacent deposits due to incomplete fusion, resulting in elongated pores. The causes of interlayer internal pore formation are ambiguous, but factors such as gas trapping, internal powder porosity, and high dilution rates are considered contributing factors. The mechanical properties of the cladding structure are also significantly affected by factors such as porosity, as pores act as crack initiation sites. Controlling the microstructure in the deposited layer is a highly complex issue. Microstructure formation is primarily influenced by thermal history and is highly sensitive to different process parameters.

[0044] To avoid the aforementioned defects, this invention proposes a strategy to improve the performance of the cladding repair microstructure while ensuring the good single-crystal integrity of the original single-crystal matrix. The key to improving the performance of the cladding repair microstructure while maintaining the good single-crystal integrity of the original single-crystal matrix lies in: 1) refining the dendritic grains of the epitaxial cladding microstructure as much as possible; 2) increasing the dislocation density within the epitaxial cladding microstructure, and having the finest possible γ′ phase structure and dense γ / γ′ interface. Related studies have shown that dislocation density directly affects the toughness and strength of metallic materials; the higher the dislocation density, the greater the material strength and the greater the relative surface hardness. Compared to the traditional cubic precipitated γ′ phase with a relatively large size (approximately 500 μm) in the matrix, the laser cladding microstructure features a large number of fine spherical γ′ phases dispersed within it. The fine γ′ phase structure and dense γ / γ′ interface significantly improve the microstructure evolution and mechanical properties of laser-clad deposited nickel-based single-crystal superalloys. To improve the mechanical properties of laser-clad epitaxial single crystals, it is necessary to consider changes in both of these conditions simultaneously. The technical solution of this invention will be clearly and completely described below with reference to various embodiments and the accompanying drawings.

[0045] This invention provides a laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials, comprising the following steps:

[0046] Step 1: Grind the nickel-based superalloy powder and oxide nanoparticles to disperse the nanoparticles in the nickel-based superalloy powder and obtain a mixed powder.

[0047] It should be noted that this invention improves the powder used in laser cladding by using a nickel-based single-crystal high-temperature alloy containing dispersed oxide nanoparticles as the raw material for preparing the epitaxial cladding structure, so as to ensure that the cladding epitaxial structure maintains the good single-crystal integrity of the original single-crystal matrix.

[0048] This invention incorporates oxide nanoparticles into nickel-based superalloy powder, which not only enhances the metallic properties of the powder but also helps refine grains and prevent solidification cracks. To fully utilize the aforementioned effects of the oxide nanoparticles on the nickel-based superalloy powder, this invention preferably employs a grinding method. The nickel-based superalloy powder and oxide nanoparticles are ground and mixed to ensure that the oxide nanoparticles are successfully and uniformly dispersed throughout the powder. The grinding process is achieved using a mechanical grinding machine, with 1 / 3 of the volume of steel balls added to an empty container. The grinding machine speed is set to 80–120 r / min, and the grinding time is 10–15 min.

[0049] To ensure the successful and uniform dispersion of oxide nanoparticles in nickel-based superalloy powder, this invention limits the mass ratio of nickel-based superalloy powder to oxide nanoparticles to 9–11:1, thereby forming a superalloy powder with completely dispersed nanoparticles. Furthermore, this invention limits the particle size of the oxide nanoparticles to 40–60 nm and the particle size of the nickel-based superalloy powder to 40–50 μm.

[0050] This invention takes into account that the melting temperature of the alloy surface is extremely high during the implementation process, usually exceeding 1300°C. Therefore, the oxide nanoparticles are preferably ZnO nanoparticles with a high melting point to ensure that the oxide nanoparticles used can be successfully doped into the epitaxial cladding structure during the laser cladding process, so as to achieve the functions of strengthening the metallic properties of nickel-based high-temperature alloy powder, refining grains, and preventing solidification cracks in the structure.

[0051] The composition of the nickel-based high-temperature alloy powder used in this invention should be adjusted according to the composition of the actual substrate to be repaired. That is, the nickel-based high-temperature alloy powder used in this invention should be homogeneous with the substrate alloy. For example, when the composition of the substrate to be repaired is second-generation high-temperature alloy DD6, the nickel-based high-temperature alloy powder used is second-generation high-temperature alloy DD6 powder.

[0052] Step 2: Pre-treat the surface of the substrate to be repaired to obtain the pre-treated substrate, and fix it on the repair platform.

[0053] It should be noted that, considering the possibility of oxide layers or other impurities on the surface of the substrate to be repaired, or unevenness on the surface, which would affect the effect of subsequent laser cladding, this invention also performs pretreatment on the surface of the substrate to be repaired to facilitate the repair process. The specific pretreatment steps are as follows:

[0054] A flat area to be repaired is obtained by mechanically cutting the substrate. Then, the surface of the substrate is polished with sandpaper and alcohol to make the surface roughness Ra 1.5 to 6.5, which is a pretreatment of the surface of the substrate. Then, it is fixed in the center of the repair platform to facilitate subsequent laser cladding.

[0055] Step 3: Load the mixed powder into the powder feeder, adjust the angle between the nozzle of the powder feeder and the surface of the substrate to be repaired to 38-42°, and set the powder feeding rate of the powder feeder.

[0056] It should be noted that before laser cladding, the mixed powder needs to be loaded into the powder feeder, and the entire powder feeding device needs to be adjusted to ensure a stable and balanced powder conveying process. The output position of the laser beam is then adjusted so that its initial beam is on the boundary of the area to be repaired on the part. At this point, the laser power is adjusted, and the CNC machine tool is adjusted, setting the scanning speed and trajectory of the laser beam. The position and angle of the powder feeder nozzle are adjusted so that the angle between the powder beam and the surface of the repair area is 38–42°, and then the powder feeding rate of the powder feeder is adjusted.

[0057] Step 4: Set the various working parameters of laser cladding, and use synchronous powder feeding to deposit the mixed powder on the surface of the substrate to be repaired to form an epitaxial cladding structure layer, thus completing the repair of the surface of the substrate to be repaired.

[0058] It should be noted that after the above preparations are completed, the various working parameters of laser cladding can be set, and then the laser cladding system can be turned on. The powder feeder nozzle moves synchronously with the laser head and performs laser processing operations according to the given trajectory. That is, it performs multi-layer epitaxial cladding growth of tissue in the area along the set route trajectory until the set repair trajectory is completed, and then the repair work is terminated.

[0059] Furthermore, to ensure good single-crystal properties of the laser epitaxial cladding growth structure, the laser cladding process parameters adopted in this invention are as follows: laser power of 200-500W, spot diameter of 700-900μm, laser scanning speed of 10-20mm / s, powder feeding rate of 10-15g / min, and defocusing amount of -300-300μm.

[0060] Example 1

[0061] Please see Figure 1 This embodiment provides a laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials, including the following steps:

[0062] In this embodiment, the domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 is used as the substrate to be repaired. Therefore, the nickel-based high-temperature alloy powder used in this invention is the domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 powder, with a particle size of 40-50 μm.

[0063] Step 1, Preparation of mixed powder

[0064] The second-generation nickel-based single crystal high-temperature alloy DD6 powder and ZnO nanoparticles were mixed at a mass ratio of 10:1 and then added to a grinder. A steel ball with a volume of 1 / 3 was added to the empty barrel. The grinder speed was set to 100 r / min and the grinding time was 8 min, so that the nanoparticles completely coated the metal powder particles to obtain a mixed powder.

[0065] The ZnO nanoparticles used in this embodiment have a particle size of 40–60 nm.

[0066] Step 2, Pretreatment of the substrate to be repaired:

[0067] The domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 was cut into single-crystal substrate sheets with dimensions of 30mm×10mm×2mm. The surface of the substrate to be repaired was then polished with sandpaper and alcohol to make the surface roughness Ra of the single-crystal substrate sheet 2.0. It was then fixed in the center of the repair platform.

[0068] Step 3, adjust the position and feeding rate of the powder feeder:

[0069] The mixed powder prepared in step 1 is loaded into the powder feeder, and the angle between the nozzle of the powder feeder and the surface of the single crystal substrate obtained in step 2 is adjusted to 40°. The powder feeding rate of the powder feeder is set to 10 g / min.

[0070] Step 4, laser cladding process:

[0071] Adjust the output position of the laser beam so that its initial beam is on the boundary of the area to be repaired on the part. At this time, adjust the power of the laser to 250W and start adjusting the CNC machine tool. Control the scanning speed of the laser beam to 10mm / s and work according to the "S" shaped scanning trajectory of traditional laser cladding. The spot diameter is 800μm and the defocusing amount is 100μm. Using a synchronous powder feeding method, the mixed powder is deposited on the surface of the single crystal substrate to form an epitaxial cladding structure layer. A complete cladding structure (cladding structure thickness of about 300μm-400μm) is formed on the surface, thus completing the repair of the surface of the single crystal substrate.

[0072] Example 2

[0073] This embodiment provides a laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials, including the following steps:

[0074] In this embodiment, the domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 is used as the substrate to be repaired. Therefore, the nickel-based high-temperature alloy powder used in this invention is the domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 powder, with a particle size of 40-50 μm.

[0075] Step 1, Preparation of mixed powder

[0076] The second-generation nickel-based single crystal high-temperature alloy DD6 powder and ZnO nanoparticles were mixed at a mass ratio of 9:1 and then added to a grinder. A steel ball with a volume of 1 / 3 was added to the empty barrel. The grinder speed was set to 80 r / min and the grinding time was 5 min, so that the nanoparticles completely coated the metal powder particles to obtain a mixed powder.

[0077] The ZnO nanoparticles used in this embodiment have a particle size of 40–60 nm.

[0078] Step 2, Pretreatment of the substrate to be repaired:

[0079] The domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 was cut into single-crystal substrate sheets with dimensions of 30mm×10mm×2mm. The surface of the substrate to be repaired was then polished with sandpaper and alcohol to make the surface roughness Ra of the single-crystal substrate sheet 1.5. It was then fixed in the center of the repair platform.

[0080] Step 3, adjust the position and feeding rate of the powder feeder:

[0081] The mixed powder prepared in step 1 is loaded into the powder feeder, and the angle between the nozzle of the powder feeder and the surface of the single crystal substrate obtained in step 2 is adjusted to 38°. The powder feeding rate of the powder feeder is set to 12 g / min.

[0082] Step 4, laser cladding process:

[0083] Adjust the output position of the laser beam so that its initial beam is on the boundary of the area to be repaired on the part. At this time, adjust the power of the laser to 200W and start adjusting the CNC machine tool. Control the scanning speed of the laser beam to 15mm / s and work according to the "S" shaped scanning trajectory of traditional laser cladding. The spot diameter is 700μm and the defocusing amount is -300μm. Using a synchronous powder feeding method, the mixed powder is deposited on the surface of the single crystal substrate to form an epitaxial cladding structure layer. A complete cladding structure (cladding structure thickness of about 300μm-400μm) is formed on the surface, thus completing the repair of the surface of the single crystal substrate.

[0084] Example 3

[0085] This embodiment provides a laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials, including the following steps:

[0086] In this embodiment, the domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 is used as the substrate to be repaired. Therefore, the nickel-based high-temperature alloy powder used in this invention is the domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 powder, with a particle size of 40-50 μm.

[0087] Step 1, Preparation of mixed powder

[0088] The second-generation nickel-based single crystal high-temperature alloy DD6 powder and ZnO nanoparticles were mixed at a mass ratio of 11:1 and then added to a grinder. A steel ball with a volume of 1 / 3 was added to the empty barrel. The grinder speed was set to 120 r / min and the grinding time was 10 min, so that the nanoparticles completely coated the metal powder particles to obtain a mixed powder.

[0089] The ZnO nanoparticles used in this embodiment have a particle size of 40–60 nm.

[0090] Step 2, Pretreatment of the substrate to be repaired:

[0091] The domestically produced second-generation nickel-based single-crystal high-temperature alloy DD6 was cut into single-crystal substrate sheets with dimensions of 30mm×10mm×2mm. The surface of the substrate to be repaired was then polished with sandpaper and alcohol to achieve a surface roughness Ra of 6.5. The substrate sheets were then fixed in the center of the repair platform.

[0092] Step 3, adjust the position and feeding rate of the powder feeder:

[0093] The mixed powder prepared in step 1 is loaded into the powder feeder, and the angle between the nozzle of the powder feeder and the surface of the single crystal substrate obtained in step 2 is adjusted to 42°. The powder feeding rate of the powder feeder is set to 15 g / min.

[0094] Step 4, laser cladding process:

[0095] Adjust the output position of the laser beam so that its initial beam is on the boundary of the area to be repaired on the part. At this time, adjust the power of the laser to 500W and start adjusting the CNC machine tool. Control the scanning speed of the laser beam to 20mm / s and work according to the "S" shaped scanning trajectory of traditional laser cladding. The spot diameter is 900μm and the defocusing amount is 300μm. Using a synchronous powder feeding method, the mixed powder is deposited on the surface of the single crystal substrate to form an epitaxial cladding structure layer. A complete cladding structure (cladding structure thickness of about 300μm-400μm) is formed on the surface, thus completing the repair of the surface of the single crystal substrate.

[0096] Comparative Example 1

[0097] The only difference between this comparative example and Example 1 is that:

[0098] The repair powder used in this invention is unmixed domestic second-generation nickel-based single-crystal high-temperature alloy DD6 powder.

[0099] Experimental Section

[0100] (I) Morphological Test

[0101] This invention uses unmixed domestically produced second-generation nickel-based single-crystal superalloy DD6 powder and the mixed powder formed by mixing domestically produced second-generation nickel-based single-crystal superalloy DD6 powder with ZnO nanoparticles in Example 1 as examples. SEM microstructure analysis was performed on both, and the test results are as follows: Figure 2-4 ,as well as Figure 5-7 As shown.

[0102] in, Figure 2 SEM image of a single nickel-based single-crystal superalloy powder at the 50 μm scale; Figure 3 SEM image of a single nickel-based single-crystal superalloy powder at the 20 μm scale; Figure 4 SEM image of a single nickel-based single-crystal superalloy powder at the 1 μm scale; Figure 5 This is a SEM image of the mixed powder in Example 1 at a scale of 50 μm; Figure 6 This is a SEM image of the mixed powder in Example 1 at a scale of 20 μm; Figure 7 This is a SEM image of the mixed powder in Example 1 at a scale of 500 nm.

[0103] And through comparison Figure 2 and Figure 5 As can be seen, through the grinding process of the present invention, ZnO nanopowder is fully incorporated into the high-temperature alloy powder, achieving the effect of complete encapsulation of the high-temperature alloy particles by the nanoparticles.

[0104] Depend on Figures 3-4 It can be seen that the microscopic surface of the unmixed high-temperature alloy is relatively smooth, and there is no powder coating on the surface.

[0105] Depend on Figures 6-7 As can be seen from the magnified microscopic surface of the nanocomposite powder spheres, there are obvious complete nanoscale particles fully dispersed on the surface of the powder spheres, indicating that the grinding process can enable zinc oxide nanoparticles to be fully dispersed on the surface of nickel-based single crystal high-temperature alloy powder.

[0106] Furthermore, taking the epitaxial cladding structure layer formed in Comparative Example 1 and the epitaxial cladding structure layer formed in Example 1 as examples, the present invention conducted SEM micromorphology analysis on their cross-sections, and the test results are as follows: Figure 8 and Figure 9 As shown, and Figure 8 and Figure 9 The scale bar is 300 μm.

[0107] And by Figure 8 and Figure 9 It can be seen that the epitaxial cladding structure of the high-temperature alloy without nanocomposite materials has dendrites growing vertically upwards, while the epitaxial cladding structure with nanocomposite materials has a grain structure that is as fine as possible. The laser cladding structure has relatively fine grains and a large number of nanoparticles precipitated and dispersed. Such grain structure and densely dispersed nanoparticles have a significant improvement on the hardness and tensile strength of laser cladding deposited nickel-based single crystal high-temperature alloys.

[0108] While ensuring the good single-crystality of the epitaxial cladding structure, the present invention significantly refines the grain size of the epitaxial cladding structure, and has a higher dislocation line distribution density inside the structure. Compared with other single-crystal epitaxial structures, it has a larger dislocation density distribution and a finer grain structure.

[0109] (II) XRD Testing

[0110] The present invention also takes the epitaxial cladding structure layer formed in Comparative Example 1 and the epitaxial cladding structure layer formed in Example 1 as examples, and performs XRD tests on them respectively, and the test results are as follows. Figure 10 As shown.

[0111] And by Figure 10 It can be seen that the laser epitaxial cladding growth structure with ZnO nanoparticles has a diffuse distribution of ZnO nanoparticles inside, and ZnO nanoparticles have been successfully deposited inside the structure.

[0112] (III) TEM Testing

[0113] The present invention also takes the epitaxial cladding structure layer formed in Comparative Example 1 and the epitaxial cladding structure layer formed in Example 1 as examples, and performs TEM tests on them respectively, and the test results are as follows: Figure 11 and Figure 12 As shown.

[0114] in, Figure 11 A high-resolution TEM image of the dislocation distribution in the epitaxial cladding structure layer formed in Comparative Example 1; Figure 12 This is a high-resolution TEM image of the dislocation distribution in the epitaxial cladding structure layer formed in Example 1.

[0115] And by Figure 11 and Figure 12 It can be seen that the dislocation lines inside the laser epitaxial cladding structure without nanocomposite are sparse and almost non-existent, while the dislocation lines inside the laser epitaxial cladding structure after nanoparticle composite are obvious and relatively dense.

[0116] (iv) Mechanical property testing

[0117] The present invention also takes the epitaxial cladding layer formed in Comparative Example 1 and the epitaxial cladding layer formed in Example 1 as examples, and respectively conducted mechanical property tests on them, and the test results are as follows. Figures 13-15 As shown.

[0118] in, Figure 13 The results show the hardness test results of the epitaxial cladding layers formed in Comparative Example 1 and Example 1; Figure 14 The Young's modulus test results are for the epitaxial cladding microstructures formed in Comparative Example 1 and Example 1. Figure 15 Load-displacement curves of the epitaxial cladding microstructure formed in Comparative Example 1 and Example 1; Figure 16 The results show the ultimate tensile strength test results of the epitaxial cladding microstructures formed in Comparative Example 1 and Example 1; Figure 17 The room temperature tensile curves of the epitaxial cladding structures formed in Comparative Example 1 and Example 1 are shown.

[0119] And by Figure 13 As can be seen, compared with Comparative Example 1, Example 1 has significantly improved the mechanical properties of the epitaxial structure while ensuring good single crystallinity of the epitaxial cladding structure, with the microhardness being increased by up to 10% compared with the matrix.

[0120] Depend on Figure 14 It can be seen that, compared with Comparative Example 1, the Young's modulus of the epitaxial structure in Example 1 is increased by nearly 32%.

[0121] And by Figures 15-17 It can be seen that, comparing the mechanical properties of laser epitaxial cladding structures using the two techniques, the structure grown by laser epitaxial cladding with nanocomposite materials exhibits superior mechanical properties in both displacement-load and ultimate tensile strength. Example 1, compared to Comparative Example 1, shows a 7% increase in ultimate tensile strength, resulting in a laser epitaxial single-crystal structure with even better performance. This provides a new technical path and approach for developing and improving laser cladding technology with higher application value.

[0122] Obviously, the above embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A laser cladding repair method for nickel-based single-crystal superalloys based on nanocomposite materials, characterized in that, Includes the following steps: Nickel-based superalloy powder and oxide nanoparticles are ground together to disperse the nanoparticles in the nickel-based superalloy powder, thereby obtaining a mixed powder. The surface of the substrate to be repaired is pretreated to obtain the pretreated substrate, and then it is fixed on the repair platform. The mixed powder is loaded into the powder feeder, and the angle between the nozzle of the powder feeder and the surface of the substrate to be repaired is adjusted to 38~42°. The powder feeding rate of the powder feeder is set. By setting the various working parameters of laser cladding and using a synchronous powder feeding method, the mixed powder is deposited on the surface of the substrate to be repaired to form an epitaxial cladding structure layer, thus completing the repair of the surface of the substrate to be repaired. The oxide nanoparticles are ZnO nanoparticles; The oxide nanoparticles have a particle size of 40~60nm; The composition of the nickel-based superalloy powder is the same as that of the substrate to be repaired; The particle size of the nickel-based high-temperature alloy powder is 40~50μm; The mass ratio of the nickel-based superalloy powder to the oxide nanoparticles is 9~11:1; The process parameters for laser cladding are as follows: The laser power is 200~500W, the spot diameter is 700~900µm, the laser scanning speed is 10~20mm / s, the powder feeding rate is 10~15g / min, and the defocusing amount is -300~300µm; The grinding process is carried out by mechanical grinding, with a grinding speed of 80~120 r / min and a grinding time of 5~10 min.

2. The method for laser cladding repair of nickel-based single-crystal superalloys as described in claim 1, characterized in that, The preprocessing is performed through the following steps: The surface of the substrate to be repaired is polished using sandpaper and alcohol to achieve a surface roughness Ra of 1.5 to 6.5.

Citation Information

Patent Citations

  • Multiphase nano ceramic particle hybrid reinforced nickel-based alloy composite material and laser forming method thereof

    CN108728695A